Severe acute pulmonary haemorrhage and haemoptysis in ten dogs following eastern brown snake (Pseudonaja textilis) envenomation: Clinical signs, treatment and outcomes. (August 2018) - Leong, Oriana S.; Padula, Andrew M.; Leister, Ellie
Abstract: This report describes a series of ten cases of fulminant pulmonary haemorrhage in dogs following envenomation by the eastern brown snake ( Pseudonaja textilis ) in south eastern Queensland, Australia. All cases were presented for veterinary treatment during 2011–2018 at a specialist veterinary emergency centre. Each case received prompt antivenom treatment and supportive care. Pulmonary haemorrhage was diagnosed based on clinical examination; overt haemoptysis; thoracic radiographic demonstration of a diffuse alveolar pattern; and, the presence of venom induced consumptive coagulopathy. The median elapsed time from hospital admission to onset of haemoptysis was 2 h (range 0–18 h). In 80% (8/10) of cases endotracheal intubation was required, whilst 20% (2/10) were successfully treated with mask oxygen supplementation alone, and 40% (4/10) received mechanical ventilation; but only 25% (1/4) of these survived to hospital discharge. Fresh frozen canine plasma was administered to 70% (7/10) of cases and 43% (3/7) of these survived. Of the total number of cases presented for treatment, 30% (3/10) survived to hospital discharge, 60% (6/10) were euthanised due to poor prognosis and 10% (1/10) died from cardiac arrest. Initial serum brown snake venom antigen levels were retrospectively measured from frozen serum samples by venom specific sandwich ELISA in two dogs at 154 ng/mL (survived) and 3607 ng/mL (euthanised); no free venom was detected post-antivenom. Dogs that survived were discharged from hospital without apparent complications. Pulmonary haemorrhage is an uncommon event following envenomation by P. textilis in dogs and has not been described in similarly envenomed humans. This case series highlights the potential for fulminant and fatal pulmonary haemorrhage in dogs following eastern brown snake envenomation. Highlights: Ten cases of eastern brown snake envenomation in dogs that experienced fulminant pulmonary haemorrhage. High case fatality or euthansia rate. Some dogs can experience potentially fatal pulmonary haemorrhage following P. textilis envenomation.